Holosene brevariasjoner i Geisdalen. En rekonstruksjon basert på kvartærgeologisk kartlegging, lichenometri og innsjøsedimenter - Andresen, Marianne Bolstad (The University of Bergen, 2015)
The purpose of this master thesis has been to reconstruct Holocene glacier fluctuations in Geisdalen. Spørteggbreen which is located in the north eastern part of the valley is a 28 km2 plateau glacier. The reconstruction is based on quaternary mapping of the valley, lichenometry on the glacier foreland, and lake sediments from the proglacial lake Geisdalsvatnet. Lichenometric dates have been correlated to other age estimates from moraines in front of glacier outlets from the Jostedalsbreen ice cap and several glaciers in Breheimen and Jotunheimen. Two piston cores and one HTH-core have been retrieved from Geisdalsvatnet and based on them a multi proxy approach has been carried out. The oldest Holocene glacial activity recorded in the valley is located in the western part where Geisdalen meets Jostedal. Several lateral moraines, about 6 km from today's glacier margin, crossing a glaciofluvial terrace that indicates a former ice-dammed lake. The meltwater from Spørteggbreen has been dammed up by a valley glacier occupying Jostedal and formed a terrace. When the valley glacier retreated, the glacier tongue of Spørteggbreen advanced and subsequently deposited moraines on top of the glaciofluvial deposits. Afterwards Spørteggbreen retreated significantly. The next glacial advance is indicated by two sets of parallel moraines about 1.2 km from today's glacier margin and interpreted as the Erdalen event. The basal part of one of the cores (GEP-214) consists of minerogenic material. Radiocarbon dates of macrofossils from the core have made it possible to construct an age-/depth model and extrapolation of the age estimates indicate that the basal part of the core correlates with the glacial episode Finse event around 8200 cal. yr BP. Following the Finse event, analysis of the core indicates that the glacier melted away from the catchment and the first reoccurrence is estimated to be around 1000 cal. yr BP. The period between 78000 - 1000 cal. yr BP is characterized by organic input interrupted by events interpreted as ...